Changing background risk and risk-taking: Evidence from the field - Linda Kleemann; Marie-Catherine Riekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
Decisions involving risk are usually taken in the presence of other insurable or non-insurable risks, the latter type called background risk. We examine how changing background risk influences risk-taking based on panel data with monthly observations from Senegalese fishermen. Fishing income is volatile and income risk depends on weather conditions and on technologies employed. To measure risktaking, we use an incentivized investment task. To measure background risk, we consider long-run wind conditions and a measure based on comparing standardized monthly income deviations from the yearly individual mean. We find that the latter measure that controls for technology choices and thus takes conscious reduction of risk exposure into account has a significant impact when overall fishing income is below average. Then, higher income risk increases risk-taking, suggesting intemperate behavior in low-income situations. This effect is stronger for poorer fishermen, highlighting the need for safety nets.
Keywords: C93; D81; O12; O13; Q22; 330; risk-taking; background risk; temperance; investment; fisheries; Senegal